Perbandingan Komunitas Burung di Lahan Perkebunan Kopi dengan Naungan Pohon Alami - Wahyu Widodo (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to compare bird communities in coffee plantation habitats with tree shade systems in natural forests or trees planted by coffee farmers. The method used is the bird encounter rate per unit time. The results showed that the quantitative ecological values ​​of birds in two coffee plantation areas were Richness Indices (RI) = 11.18, Diversity Indices (DI) = 3.71, Sorensen Indices (SI) = 45.5% and the Similarity Index of Two Habitats (ISE) = 24.3%. As many as 65% of bird species in both coffee plantations are potential insectivorous birds. In conclusion, three of the 85 bird species encountered during the study had a near-threatened (NT) conservation status, namely Loriculus pusillus, Oriolus xanthonotus, and Ficedula dumetoria. One species is categorized as Endangered (EN) namely Spizaetus bartelsi and the other species is a migratory bird, namely Muscicapa dauurica. Keywords: Insectivorous Birds, Habitat, Coffee Plantation, Ecological Value, Conservation Status